SOLUBILITY AND DISSOLUTION ENHANCEMENT OF IVACAFTOR TABLETS BY USING SOLID DISPERSION TECHNIQUE OF HOT-MELT EXTRUSION - A DESIGN OF EXPERIMENTAL APPROACH - Guntaka, Purnachandra Reddy; Lankalapalli, Srinivas (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The objective was to improve the solubility and dissolution of ivacaftor tablets by using solid dispersion (SD) technique. Methods: Ivacaftor is practically insoluble (<0.001 mg/mL) over pH value of 3.0–7.5 due to low solubility, and it shows poor bioavailability after oral administration. Therefore, SDs of Ivacaftor were prepared by SD technique of hot-melt extrusion (HME) by adding different polymers such as Soluplus, Hypromellose 5 cps, and Copovidone with surfactants sodium lauryl sulfate, poloxamer, and polysorbate 80 to enhance its solubility. Results: After the analysis of Fourier-transform infrared spectrometry, X-ray diffraction, and differential scanning calorimetry of SDs by HME shows a converted in crystalline structure form to an amorphous structure form of Ivacaftor. The results show that the formulation of Ivacaftor SDs by HMT has enhanced the solubility and dissolution of Ivacaftor. Conclusion: In the present study, the SDs of the poorly soluble drug substance Ivacaftor were successfully prepared using HME. The in vitro dissolution test shows a significant increase in dissolution rate of SDs prepared by HME (95%) in formulation FHM8 compared with plain Ivacaftor (9%) within 30 min.